Calendar Anomalies In The Malaysian Stock Market - Venus, Khim-Sen Liew; Ricky, Chee-Jiun Chia; Syed Azizi Wafa, Syed Khalid Wafa (Universiti Malaysia Sabah (UMS), 2006)
This study examines the calendar anomalies in the Malaysian stock market. Using various generalized autoregressive conditional heteroskedasticity models; this study reveals the different anomaly patterns in this market for before, during and after the Asian financial crisis periods. Among other important findings, the evidence of negative Monday returns in post-crisis period is consistent with the related literature. However, this study finds no evidence of a January effect or any other monthly seasonality. The current empirical findings on the mean returns and their volatility in the Malaysian stock market could be useful in designing trading strategies and drawing investment decisions.